ASPEK-ASPEK HUKUM HUMANITER DALAM KEJAHATAN PERANG YANG DILAKUKAN OLEH ANGGOTA DINAS ANGKATAN LAUT DALAM KONFLIK INTERNASIONAL - Devy Sondakh (terAs Law Review : Jurnal Hukum Humaniter dan HAM, 2008)
This article focuses on the enforcement of international humanitarian law through the prosecution and punishment of individuals accused of violations of international humanitarian law by national tribunals, especially about the doctrinal contributions regarding war crimes committed by navy officers at national tribunals. The author also shows principles that has developed by the ICC's Statute, such as legality principle, individual criminal responsibility, superior order, fair trial, no survivor, and act of state doctrine.